Experimental characterization of next‐generation expanded‐bed adsorbents for capture of a recombinant protein expressed in high‐cell‐density yeast fermentation. (1st October 2013) - Kelly, William; Garcia, Phillip; McDermott, Stefanie; Mullen, Peter; Kamguia, Guy; Jones, Gerard; Ubiera, Antonio; Göklen, Kent
Abstract: Expanded‐bed adsorption (EBA) can be particularly useful in protein recovery from high‐cell‐density fermentation broth where conventional methods for harvest and clarification, such as continuous centrifugation and depth filtration, demand long processing times and are associated with high costs. In this work, the use of next‐generation high‐particle‐density EBA adsorbents, including two mixed‐mode resins, for the direct capture of a recombinant protein expressed in yeast at high cell densities is evaluated. Using classical experimental approaches and under different conditions (pH, salt, etc.), Langmuir isotherm parameters for these resins are obtained along with pore diffusivity values. Additional batch adsorption studies with Fastline® MabDirect, the resin that demonstrated the highest static binding capacity for the recombinant protein of interest under the conditions evaluated in this study, indicate competitive binding of nontarget proteins and approximately a 30% reduction in equilibrium binding capacity to 50 mg/mL settled bed in the presence of a 5%–10% cell concentration. Packed‐bed (PB) dynamic binding capacities for the MabDirect resin (25–40 mg/mL PB) were significantly higher than for the Fastline® HSA resin and for the MabDirect MM resin in expanded‐bed mode (5–10 mg/mL settled bed). Bed expansion behavior for the mMabDirect MM resin along with process yield and eluate purity are identified as a function of linear velocity and cell density, demonstrating process feasibility for pilot scale use.